2008
DOI: 10.1007/s10340-008-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Two-spotted spider mite in Cyprus: ineffective acaricides, causes and considerations

Abstract: Growers of greenhouse roses in Cyprus have recently reported failures of several acaricides against twospotted spider mite (Tetranychus urticae Koch). To verify the cause of these failures we evaluated the eVectiveness of seven acaricides against two rose and two cucumber spider mite populations in the laboratory. The acaricides included in our study represented the most important mode of action groups registered for use in greenhouses on the island. Label rates of all seven acaricides (abamectin, clofentezine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nevertheless, problems with T. urticae are frequently reported in protected crops, in particular in rose greenhouses, where many recently introduced acaricides show a progressive loss of effectiveness after only a few years of use. This situation seems to reflect that reported in other countries (e.g., Stavrinides and Hadjistylli 2009;Khajehali et al 2011). European floricultural production accounts for 40-50% of the world production (19.5 billion in 2009).…”
Section: Introductionmentioning
confidence: 52%
“…Nevertheless, problems with T. urticae are frequently reported in protected crops, in particular in rose greenhouses, where many recently introduced acaricides show a progressive loss of effectiveness after only a few years of use. This situation seems to reflect that reported in other countries (e.g., Stavrinides and Hadjistylli 2009;Khajehali et al 2011). European floricultural production accounts for 40-50% of the world production (19.5 billion in 2009).…”
Section: Introductionmentioning
confidence: 52%
“…No significant difference in mean generation time (T) was observed among the different treatments. 10 34.97 ± 2.31 b 2.97 ± 0.11 a 11.57± 0.42 ab LC 30 27.57 ± 1.01 c 2.95 ± 0.13 a 9.60± 0.38 b §Values are shown as mean ± SE. Lower case letters indicate significant difference between different treatments (P < 0.05).…”
Section: Sublethal Effect Of Fluralaner On Tssm Eggsmentioning
confidence: 99%
“…TSSM has high reproductive rates and a short life history, develops quickly and can lead to total yield loss in host crops if not be controlled in a timely manner . TSSM has developed resistance to a broad range of chemical classes of acaricides and is considered as ‘resistance champion’ in terms of the total number of compounds to which its populations have become resistant . For example, the eggs, larvae and female adults of TSSM have developed 56 771‐, 42 378‐ and 4989‐fold resistance to abamectin, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, spider mites develop resistance to pesticides rapidly (Croft and van de Baan 1988) and TSM resistance to over 80 pesticides has been reported to date from around the world, spanning most major chemical groups (APRD 2007). TSM resistance problems are of special interest in Cyprus, where a recent study suggested that some populations are resistant to the great majority of acaricides registered for use on the island (Stavrinides and Hadjistylli 2009).…”
Section: Introductionmentioning
confidence: 99%